The Relationship of Macronutrient Intake and Sleep Duration to Nutritional Status in Students - Noorsy, Nadhira Ahadea; Rakhma, Luluk Ria (Newinera Publisher, 2024)
Nutritional status is a state of health in a person's body which is caused by consumption, absorption and use of food nutrients. Based on the results of the 2023 Indonesian Health Survey, it shows that Central Java province is one of the provinces that has a prevalence of underweight adults (age > 18 years) above the national prevalence of 8.9%. The adult population has 9.0% undernutrition or underweight, 13.5% overnutrition and 22.5% obesity. Nutritional status can also be influenced by sleep duration. Sleep duration is an important regulator of body weight and metabolism. Objective: To determine the relationship between macronutrient intake and sleep duration on nutritional status. This type of research was observational using cross-sectional. The number of research subjects was 101 students taken by random sampling. The data used in this study were primary data such as age, gender, food intake for 3 non-consecutive days, sleep duration and nutritional status. Statistical tests use the Chi-Square test. Students with poor protein intake and normal status were (35.4%). Students with poor fat intake and underweight nutritional status were (38.1%). Students with good carbohydrate intake and normal nutritional status were (64.9%). And students with a sleep duration of >6 hours with normal nutritional status were (48.8%). There is a relationship between protein intake (p=0.028), fat (p=0.003), carbohydrates (p=0.024) and sleep duration (p=0.048) on nutritional status.